Diagnosis and Therapeutic Management of Anaplasmosis in Bovines - Morwal, Dr. Sandhya; Kumar, Kuldeep (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
Present investigation was done in anaplasmosis affected seven indigenous cattle and two buffaloes to determine the haemato-biochemical alteration and to know about the therapeutic response of imidocarb dipropionate in anaplasmosis affected animals. Haemato-biochemical examination revealed significant lower Hb, PCV, TEC, lymphocyte count, platelets, glucose, albumin and TP whereas total leucocytes count, neutrophils count, eosinophils count, AST, ALT, LDH total bilirubin, globulin and alkaline phosphatase were found significant higher in anaplasmosis affected cattle and buffaloes as compared to healthy control animals. Diagnosis of anaplasmosis was based upon peripheral blood smear examination which showed presence of dot-like protozoa at the periphery of the erythrocytes. Observed clinical manifestation in affected cattle and buffaloes were inappetence or anorexia, intermittent fever, tachycardia, increased respiration rate, muscular weakness, emaciation, paler conjunctiva and presence of ticks on body surface. Treatment with imidocarb dipropionate and other supportive therapy was found very effective in anaplasmosis affected animals. In early diagnosis and treatment prognosis is good but severely affected or untreated animals may die.